GENDER EQUALITY IN NATIONAL DEFENSE POLICY: A COMPARATIVE STUDY IN ASEAN COUNTRIES - Sarjito, Aris (Journal of Governance and Public Administration, 2025)
This study aims to understand how gender integration policies in the defense sector in ASEAN countries and analyze the successes and challenges faced in implementing these policies. The research method used is a qualitative approach with comparative policy analysis, relying on policy documents, government reports, academic literature, and insights from experts. The results of the study show that countries such as the Philippines and Indonesia have shown significant progress in gender integration in their defense institutions, while countries such as Myanmar, Brunei, Cambodia, and Laos still face cultural barriers and a lack of adequate policies. Despite the existence of policies, in countries such as Thailand, Vietnam, Malaysia, and Singapore, women still face limitations in leadership roles and access to higher positions. The conclusion of this study is that strong policies need to be supported by political and social commitment to overcome cultural and structural barriers. The success of gender policies in the defense sector depends heavily on substantive implementation and strong leadership support to create an inclusive and effective defense force. Keywords: Gender Integration Policy, ASEAN Defense Sector, Comparative Policy Analysis, Gender Equality, Policy Implementation